PENYELESAIAN MASALAH JOB SHOP MENGGUNAKAN ALGORITMA GENETIKA - Satriyo Adhy; Kushartantya Kushartantya (Department of Informatics, Universitas Diponegoro, 2010)
Job Shop Scheduling Problem (JSP) is a problem of work scheduling that can be describe by one or several job that have to be done by one or several source, each job contain of several operation that has to be done without interuption in several time and spesific source. Many kind algorithm can be use to solve JSP, one of them is genetic algorithm. Genetic Algorithm use in this final project to solve JSP. Genetic algorithm step begin with individual representation, initial population, reproduction and selection process, crossover gen, mutation gen and evaluation. Solving JSP with genetic algorithm can give a schedule of job in source with optimal time process, then Delphi 6 software use to make the solving program. Key Word : Job Shop Scheduling Problem (JSP), Genetic Algorithm, Delphi 6